Applications of fire engineering : proceedings of the International Conference of Applications of Structural Fire Engineering (ASFE 2017), September 7-8, 2017, Manchester, United Kingdom /: proceedings of the International Conference of Applications of Structural Fire Engineering (ASFE 2017), September 7-8, 2017, Manchester, United Kingdom. (2017) - Unknown
No abstract available